2004
DOI: 10.1002/hlca.200490085
|View full text |Cite
|
Sign up to set email alerts
|

Chemie freier cyclischer vicinaler Tricarbonyl‐Verbindungen (‘1,2,3‐Trione’). Teil 3

Abstract: The central CO groups of cyclic 1,2,3-triones possess outstanding electrophilic (electron-pair-accepting) as well as oxidizing (one-electron-accepting) properties. Thus, 1,2,3-triones are chemically related to 1,2-and 1,4benzoquinones. Whereas polar reactions with carbanion-like (electron rich) species give rise to nucleophilic addition reactions to CO groups under exclusive C,C-bond formation, SET (single-electron transfer) or redox reactions effect a partial −carbonyl Umpolung× via ketyl intermediates (C,C-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 122 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…It has been reported that vic-triketones react with enamines. 45 For the present case, it was found that monohydrate 104 reacts with enamine 105 without addition of dehydrating agents. Aldol 106 was formed stereoselectively, with the enamine approaching the central carbonyl group of the in-situ formed vic-triketone from the face opposite to the TBDPS ether.…”
Section: Short Review Syn Thesismentioning
confidence: 51%
See 1 more Smart Citation
“…It has been reported that vic-triketones react with enamines. 45 For the present case, it was found that monohydrate 104 reacts with enamine 105 without addition of dehydrating agents. Aldol 106 was formed stereoselectively, with the enamine approaching the central carbonyl group of the in-situ formed vic-triketone from the face opposite to the TBDPS ether.…”
Section: Short Review Syn Thesismentioning
confidence: 51%
“…25 The 2,3,7-triketo ester 41 used for cyclisation was prepared from enol diazoacetate 40 via Mukaiyama-Michael reaction followed by oxidation with DMDO and dehydration under reduced pressure (Scheme 8). According to whether a Brønsted or Lewis acid was used in the subsequent cyclisation step, the syn- (44) or anti-product (45) was obtained selectively. As suggested by the authors, this diastereoselectivity arises from different ways of carbonyl activation.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…Schank et al have shown that free cyclic vicinal triketones react with enamines. 15 For the present case, it was found, that the monohydrate 9 reacts with the morpholine enamine 14 16 without any additive at room temperature to produce the desired aldol 13.…”
mentioning
confidence: 64%
“…Although we could not identify the oxidation agent required in this reaction, the most plausible one is considered to be ninhydrin, based on the result that 4 was obtained even when the reaction was carried out under nitrogen. Ninhydrin itself could participate in oxidation [13], because the C2 position of ninhydrin has “umpolung” ability. The carbocation at C2, resulting from the release of the OH group as an anion, should be stabilized by accepting electrons to be converted to a carbanion.…”
Section: Resultsmentioning
confidence: 99%